Cost‐effectiveness analysis of empagliflozin versus sitagliptin as second‐line therapy for treatment in patients with type 2 diabetes in the United States. Issue 3 (15th December 2020) - Reifsnider, Odette; Kansal, Anuraag; Pimple, Pratik; Aponte‐Ribero, Valerie; Brand, Sarah; Shetty, Sharash
Abstract: Aim: To estimate the cost‐effectiveness of sequential addition of empagliflozin versus sitagliptin after metformin in patients with type 2 diabetes (T2D) with or without cardiovascular disease (CVD) from the perspective of the US healthcare payer. Methods: An individual simulation model predicted lifetime diabetes‐related complications, using UKPDS‐OM2 equations in patients without CVD, and EMPA‐REG OUTCOME equations in patients with CVD. Additional US‐based sources informed inputs for population characteristics, adverse events, non‐CV death, treatment escalation, quality of life and costs. Costs and quality‐adjusted life‐years (QALYs) were discounted 3.0% annually. Results: The incremental cost‐effectiveness ratio (ICER) for second‐line empagliflozin versus sitagliptin in the overall T2D population was 6967/QALY. Empagliflozin led to longer CVD‐free survival (0.07 years) and an 11% reduction in CV death in patients with CVD compared with sitagliptin. Empagliflozin resulted in greater benefits with greater costs in patients with versus without baseline CVD, yielding ICERs of 3589/QALY versus 12 577/QALY, respectively. Results were consistent across a range of deterministic and probabilistic sensitivity analyses and scenarios. Conclusion: Compared with sitagliptin, empagliflozin was cost‐effective (at 50 000/QALY US threshold) as a second‐line treatment to metformin for T2D patients with or without CVD in the United States. Our findings lend additional support for more widespread adoption of guidelines by healthcare decision‐makers for T2D treatment.